Collaborative water management across England – An overview of the Catchment Based Approach. Issue 112 (October 2020) - Collins, Rob; Johnson, David; Crilly, Damian; Rickard, Arlin; Neal, Luke; Morse, Ali; Walker, Michelle; Lear, Rosie; Deasy, Clare; Paling, Nick; Anderton, Sarah; Ryder, Chris; et al.
Highlights: The Catchment Based Approach embeds a collaborative approach to water management River catchment partnerships are established across the whole of England Multi-sector organisations work collaboratively to deliver environmental benefits A national framework of support drives capacity and expertise in the partnerships Challenges exist but the approach can play a key role in catchment management Abstract: The Catchment Based Approach (CaBA) was established in 2013 to drive collaborative water management across England. Globally unique in its national coverage, CaBA encompasses 106 river catchment partnerships that either incorporate or work with a range of cross-sector partner organisations including environmental organisations, Government agencies, water companies, local authorities, businesses and civil society. The partnerships work through consensus to build social capital and deliver environmental improvements. Because of the variety of stakeholders and interests represented, partnerships attract a range of funds, multiplying the core monies they receive from Government. A National Support group, several thematic working groups and a team of technical specialists help to build expertise within partnerships. Supported by data and evidence, including that derived through citizen science, the partnerships have developed catchment plans that capture priorities for action. Challenges of legitimacy, funding, integration with England's wider water management framework, and the monitoring of outcomes remain. Future opportunities exist, including closer alignment with academia and the potential for CaBA to undertake a key role in delivering the UK Government's 25-Year Environment Plan. Several lessons learnt from the CaBA approach may be applicable internationally.